Diet effects on colonic health influence the efficacy of Bin1 mAb immunotherapy for ulcerative colitis - Sunil Thomas; Nickey Dilbarov; Joseph Kelly; Giancarlo Mercogliano; George C. Prendergast (Scientific Reports, 2023)
Abstract Ulcerative colitis (UC) is an idiopathic disease of the large intestine linked to high fat-high protein diets, a dysbiotic microbiome, and a metabolome linked to diet and/or aberrant circadian rhythms associated with poor sleeping patterns. Understanding diet-affected factors that negatively influence colonic health may offer new insights into how to prevent UC and enhance the efficacy of UC immunotherapy. In this preclinical study, we found that standard or high fiber diets in mice positively influenced their colonic health, whereas a high fat-high protein diet negatively influenced colonic health, consistent with clinical findings. Animals fed a high fat/high protein diet experienced obesity and a reduced colon length, illustrating a phenotype we suggest calling peinosis [hunger-like-condition; Greek, peina: hunger; osis: condition], as marked by a lack of nutrient energy remaining in fecal pellets. Notably, a high fat/high protein diet also led to signs of muscle weakness that could not be explained fully by weight gain. In contrast, mice on a high fiber diet ranked highest compared to other diets in terms of colon length and lack of muscle weakness. That said, mice on a high fiber diet were more prone to UC and toxic responses to immunotherapy, consistent with clinical observations. Recent studies have suggested that a standard diet may be needed to support the efficacy of immunotherapeutic drugs used to prevent and treat UC. Here we observed that protection against UC by Bin1 mAb, a passive UC immunotherapy that acts by coordinately enforcing intestinal barrier function, protecting enteric neurons, and normalizing the microbiome, was associated with increased colonic levels of healthful short-chain fatty acids (SCFA), particularly butyric acid and propionic acid, which help enforce intestinal barrier function. This work offers a preclinical platform to investigate how diet affects UC immunotherapy and the potential of dietary SCFA supplements to enhance it. Further, it suggests that the beneficial effects of passive immunotherapy by Bin1 mAb in UC treatment may be mediated to some extent by promoting increased levels of healthful SCFA.